Panorama city ebook A novel. - Wilson, Antoine (2021)
"As enjoyable a comic novel as I have read all year, a coming of age story that vividly captures the modern world through innocent eyes." — Largehearted Boy Oppen Porter thinks he's dying. (He's not.) From his hospital bed, with tape recorder in hand, he unspools his tale for the benefit of his unborn son, the tale of his forty-day journey from innocence to experience, from self-described "slow absorber" to man of the world. What follows is a trip through modern-day southern California that establishes Panorama City as "an astonishing narrative that offers the pleasures of irony without the sting . . . The great triumph of the book is that Oppen matures without spoiling. He comes to affirm the integrity of his innocence, which is its own wisdom" ( Los Angeles Review of Books ). "Makes you see the world afresh . . . delightful." — The New York Times Book Review "Often very funny. It is filled with joy and wonder, and a sort of goodness you had stopped believing might even be possible." —Peter Carey, Booker Prize–winning author "Though it takes place in down-at-heel Panorama City with its crappy burger franchises and abandoned shopping carts, The World According to Oppen is full of wonders and mysteries." —Stewart O'Nan, national bestselling author "Charming, absurd, very funny, and best of all, human through and through." —Paul Harding, Pulitzer Prize–winning author "Antoine Wilson draws us into the weird, wonderful world of Oppen Porter, whose advice and lessons are jarringly original, funny, and moving." —Steve Hely, winner of the Thurber Award